In-Vitro Inhibitory Activities Bifidobacterium Spp. On Campylobacter Jejuni Isolated From Chickens - Omar, Rohaidah (2001)
Poultry meat is frequently contaminated with Campylobaeter jejuni and is considered to be a significant source for campylobacteriosis in man. Various possible strategies to protect chicks against C. jejuni colonisation are currently under investigation throughout the world. The use of antagonistic flora has been proposed as one of the approaches to reduce chicken intestinal colonisation by C. jejuni. Hence, this study was undertaken to identify Bifidobaeterium spp. which has been known for its antagonistic activity against many pathogenic bacteria. Bifidobacteria isolated from chickens were screened for the expression of in-vitro anti-Co jejuni activities, their antibiotic susceptibility and the anti-Co jejuni substances involved. Chickens from three broiler farms and four different flocks of village chickens were sampled for four consecutive weeks to determine the presence of Bifidobaeterium spp. It was found that Trypticase Phytone Yeast (TPY) medium with an adjusted pH of 5.2-5.5 allowed good growth of bifidobacteria and substantially inhibited growth of other contaminating facultative anaerobic organisms. A total of 57.7% (56/97) of Bifidobacterium spp isolates were obtained, of which 23.2% (13/56) were B. animalis. The organism was not isolated in oneweek-old chicks, however was detectable in two-week-old chicks. There was no significant difference (P>O.05) in variations of the total bifidobacteria isolated with the age of birds or farms in broiler or village chickens. Almost 79% (44/56) of bifidobacteria isolates possessed various degree of in-vitro anti-c. jejuni activities, and 19.6% (11/56) of the isolates demonstrated marked inhibition. All B. animalis isolates (13/13) exerted the inhibitory activities against C. jejuni. The antibiotic susceptibility test results indicated that bifidobacteria isolates were susceptible to erythromycin and ampicillin and resistant to nalidixic acid, gentamicin and streptomycin. They showed variable susceptibility to chloramphenicol, tetracycline and neomycin. The inhibitory activities produced by bifidobacteria isolates were possibly ascribed to the production of organic acids in particular acetic acid, and though not clearly shown, perhaps production of bacteriocins-like substances was also partially responsible for the inhibitory effects. However, the possible influence of hydrogen peroxide and other unknown inhibitory substances has not been excluded. Further research is needed to study the existence of such substances and to clarify the protective ability of bifidobacteria isolates, which may have potential to reduce intestinal colonisation by C. jejuni in chickens.